(untitled) (Scientific journal of the Fergana State University, 2026)
The article provides brief information on the results of the anatomical identification of wood remains discovered during archaeological research at the Xonobod-1 cemetery between 2020 and 2023. This study is one of the initial works on the identification of wood species from the Early Iron Age in the Fergana Valley. Based on the findings, a brief comparative analysis was conducted between local (wild) and cultivated species.